Survival and mortality in cerebral palsy: observations to the sixth decade from a data linkage study of a total population register and National Death Index - Blair, Eve; Langdon, Katherine; McIntyre, Sarah; Lawrence, David; Watson, Linda (BMC neurology, 2019)
Background Likely duration of survival of children described as having cerebral palsy is of considerable interest to individuals with cerebral palsy, their families, carers, health professionals, health economists and insurers. The aim of this paper is to describe patterns of survival and mortality to the sixth decade in a geographically defined population of people with cerebral palsy stratified according to the clinical description of their impairments in early childhood. Methods Identifiers of persons born in Western Australia 1956–2011, registered with cerebral palsy on the Western Australian Register of Developmental Anomalies and surviving at least 12 months, were linked to the Australian National Death Index in December 2014. Patterns of mortality were investigated using survival analysis methods. Results Of 3185 eligible persons, 436 (13.7%) had died. Of that sample the 22% with the mildest impairment had survival patterns similar to the general population. Mortality increased with increasing severity of impairment. Of 349 (75%) with available cause of death data, 58.6% were attributed to respiratory causes, including 171 (49%) to pneumonia at a mean age of 14.6 (sd 13.4) years of which 77 (45%) were attributed to aspiration. For the most severely impaired, early childhood mortality increased in succeeding decades of birth cohorts from 1950s to 1990 with 20% dying by 4 years of age in the 1981–1990 birth cohort; it then decreased for subsequent birth cohorts, 20% mortality not being attained until 15 years of age. However by 20 years of age mortality of the most severely impaired born in the 1991–2000 birth cohort exceeded that of all other birth cohorts. Remaining life expectancies by age to 50 years have been estimated for two strata with more severe impairments. Conclusion For 22% of individuals with cerebral palsy with mild impairment survival to 58 years is similar to that of the general population. Since 1990 mortality for those with severe cerebral palsy in Western Australia has tended to shift from childhood to early adulthood.